1960
DOI: 10.1002/jsfa.2740110204
|View full text |Cite
|
Sign up to set email alerts
|

The amino‐acid composition of processed bones and meat

Abstract: Quantitative amino‐acid analyses were made by ion‐exchange chromatography on two samples of commercial feeding meals containing high contents of meat and bone, respectively, after processing in an Iwel cooker and acid hydrolysis. The processed bones had an amino‐acid composition close to that of collagen with slightly larger amounts of most essential amino‐acids. The meat material contained significantly higher amounts of essential amino‐acids than the processed bones and had an overall composition intermediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

1962
1962
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 14 publications
(1 reference statement)
2
18
0
Order By: Relevance
“…3 Because the fiber sources and amounts used in the present study were tightly controlled, differences in total tract apparent macronutrient digestibility were likely not due to fiber but to the higher concentration of animal fiber (ie, collagen) in the chicken-based versus beef-based diets, which was also considered in another study. 36 Fecal fermentative end-product concentrations can be used to infer the degree of protein and carbohydrate fermentation in the large bowel. Carbohydrate fermentation by colonic microbes primarily produces SCFAs in the large intestine, providing an important energy source for colonocytes.…”
Section: Discussionmentioning
confidence: 99%
“…3 Because the fiber sources and amounts used in the present study were tightly controlled, differences in total tract apparent macronutrient digestibility were likely not due to fiber but to the higher concentration of animal fiber (ie, collagen) in the chicken-based versus beef-based diets, which was also considered in another study. 36 Fecal fermentative end-product concentrations can be used to infer the degree of protein and carbohydrate fermentation in the large bowel. Carbohydrate fermentation by colonic microbes primarily produces SCFAs in the large intestine, providing an important energy source for colonocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Like blood meal, MBM is a good source of lysine. However, MBM may contain between 50 and 65% collagen (Eastoe and Long, 1960), which is devoid of tryptophan and low in methionine (Atkinson and Carpenter, 1970).…”
Section: Methodsmentioning
confidence: 99%
“…Meat and bone meal varies in ruminal escape protein, amino acid composition, and amino acid availability (Knabe et al, 1989;Gibb et al, 1991). This may be the result of heat damage during rendering (Leibholz, 1979;Batterham and Darnell, 1986;Knabe et al, 1989) and(or) the type of tissues rendered (Eastoe and Long, 1960;Atkinson and Carpenter, 1970). Gibb et al (1991) reported higher escape protein values for MBM made from bones than MBM made from viscera or deadstock.…”
Section: Introductionmentioning
confidence: 99%
“…Collagen is the major protein in bone, connective tissue, cartilage and tendon. Eastoe and Long [21] found that collagen is severely deficient in most indispensable amino acids and poorly digested because of the low level of collagenase in digestive tract.…”
Section: Resultsmentioning
confidence: 99%